2012
DOI: 10.4236/ijg.2012.32042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Climate Change in the Coastal Zone of Eastern China, against the Background of Global Climate Change over the Last Fifty Years: Case Study of Shandong Peninsula, China

Abstract: The climate change in Shandong Peninsula, China was analyzed in this paper by the non-parametric Mann-Kendall test, Accumulated Difference Curve and Order Cluster Analysis methods, based upon the datas of annual mean, maximum and minimum temperature and annual precipitation, precipitation from June to September over the past 50 years. Results obtained showed a number of observations: 1) The annual mean temperature of Shandong Peninsula showed a significant increasing trend, with a distinct abrupt change point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It showed a general upward stream flow trends, barring a few Northwestern and Southeastern regions exhibited downward stream flow trends. The stream flow data collected from 11 Canadian gauging stations for 30-50 years were analyzed and it was observed that during this period, the average annual stream flow decreased for southern cities and the average monthly stream flow frequently decreased for all stations [14]. Similarly, it was observed on the basis of analyzing 31 years long monthly stream flow data for 26 Turkish basins which indicated downward stream flow trends.…”
Section: Introductionmentioning
confidence: 82%
“…It showed a general upward stream flow trends, barring a few Northwestern and Southeastern regions exhibited downward stream flow trends. The stream flow data collected from 11 Canadian gauging stations for 30-50 years were analyzed and it was observed that during this period, the average annual stream flow decreased for southern cities and the average monthly stream flow frequently decreased for all stations [14]. Similarly, it was observed on the basis of analyzing 31 years long monthly stream flow data for 26 Turkish basins which indicated downward stream flow trends.…”
Section: Introductionmentioning
confidence: 82%
“…Based on linear tendency estimate method (Tian et al, 2011), an analysis on the runoff changing process and long-term trend is made of the main control hydrological stations of the Tarim River Basin (as shown in Figure 2). The research results shows that, among the original rivers of Tarim River, a significant increase in the annual runoff of Aksu River and Yarkant River, a slight increase in Hotian River and an obvious decrease in the Tarim River mainstream.…”
Section: Runoff Trends and Cause Analysismentioning
confidence: 99%